2022
DOI: 10.1021/acssuschemeng.2c05298
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Self-Assembly of Bio-Based Flame Retardants for Fire-Retardant, Smoke-Suppressive, and Toughened Polylactic Acid

Abstract: Incorporating bio-based flame retardants into polylactic acid (PLA) for improving its fire retarding performance has always been attractive to researchers worldwide, while the synthesis of bio-based flame retardants always involves organic solvents. The drawbacks of bio-based flame retardants are also nonignorable, such as strong hydrophilicity, aggregation, and deterioration of the mechanical properties of PLA. Here, the biobased flame retardant APP@CS@Si was assembled in the water phase with ammonium polypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The I D / I G values of EP/3HOF-FJU-1, EP/6HOF-FJU-1, EP/9HOF-FJU-1, and EP/3HOF-FJU-1A are 2.91, 2.51, 2.24, and 2.54, respectively, and they are all lower than that of pure EP (3.11). The results show that the increase in FR filler leads to a higher degree of graphitization of the char layer, indicating that the in situ-generated HOF-FJU-1 has a beneficial effect in the formation of high-quality char layers …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The I D / I G values of EP/3HOF-FJU-1, EP/6HOF-FJU-1, EP/9HOF-FJU-1, and EP/3HOF-FJU-1A are 2.91, 2.51, 2.24, and 2.54, respectively, and they are all lower than that of pure EP (3.11). The results show that the increase in FR filler leads to a higher degree of graphitization of the char layer, indicating that the in situ-generated HOF-FJU-1 has a beneficial effect in the formation of high-quality char layers …”
Section: Resultsmentioning
confidence: 96%
“…The results show that the increase in FR filler leads to a higher degree of graphitization of the char layer, indicating that the in situgenerated HOF-FJU-1 has a beneficial effect in the formation of high-quality char layers. 65 In addition, the char residue was further analyzed using XPS. The XPS results of the char residue for EP composites are shown in Figure 8.…”
Section: Char Residue Analysis Of Ep Compositesmentioning
confidence: 99%
“…The main pyrolysis product in the first stage is water, and the products in the second stage are water and ammonia. Combined with the XPS analysis of the char residue after TGA (Figure d), the peaks around 134, 133, and 132 eV are attributed to C–O–P, P 2 O 7 4– , and P–N, respectively. …”
Section: Resultsmentioning
confidence: 99%
“…The TPP@ PVDF/SiO 2 /GO separator after combustion exhibited high graphitized carbon content, which also indicated that combustion promoted the formation of graphitized carbon and thus effectively improved thermal resistance and heat transfer. 59 Hence, TPP mainly played the role of fire extinguishing to prevent the temperature around the separator from further rising and heat transfer, which was like a "sword of fire extinguishing". GO and SiO 2 enhanced the thermal stability of the separator, and at the same time, GO provided a protective layer to isolate heat, acting as a "shield"; thus, the two factors finally made the TPP@PVDF/SiO 2 /GO separator exhibit an excellent fire prevention effect, as shown in Figure 3d.…”
Section: Flame-retardant Property and Thermal Stabilitymentioning
confidence: 99%